Hormonal Crossroads in Inborn Errors of the Metabolism Impact of Puberty and Dietary Interventions on Metabolic Health - Thomas Lundqvist; Rasmus Stenlid; Maria Halldin (Metabolites)
Background/Objectives: Inborn errors of metabolism (IEMs) represent a diverse group of genetic disorders characterized by enzymatic defects that disrupt metabolic pathways, leading to toxic metabolite accumulation, deficits, or impaired macromolecule synthesis. While strict dietary interventions are critical for managing many of these conditions, hormonal and metabolic changes during puberty introduce new challenges. Advancements in early diagnosis and treatment have significantly extended the lifespan of individuals with IEMs. However, this increased longevity is associated with heightened risks of new medical problems, including obesity, insulin resistance, and type 2 diabetes mellitus (T2DM), as these complications share mechanistic features with those seen in obesity and T2DM. Methods: This mini-review examines current knowledge of the intricate interplay between pubertal hormones and metabolic pathways in IEM patients. Results: We address critical questions, such as if puberty intensifies the risk of metabolic derangements in these individuals and if there is a metabolic intersection where these disorders converge, leading to shared complications. We highlight the impact of puberty-induced hormonal fluctuations, such as growth hormone (GH) surges and sex steroid activity, on disorders like phenylketonuria, urea cycle defects, and fatty acid oxidation disorders. Moreover, we explore the role of dietary interventions in mitigating or exacerbating these effects, emphasizing the importance of balancing nutritional needs during growth spurts. Conclusions: A multidisciplinary approach integrating endocrinology, nutrition, and emerging therapies is advocated to optimize metabolic health during puberty. Addressing these challenges is critical for improving long-term outcomes for individuals with IEMs, particularly during this pivotal developmental phase.